PENGARUH PEMELIHARAAN MESIN DAN PRODUKSI TEPAT WAKTU TERHADAP VOLUME PRODUKSI PADA PT. LAMBANG UTAMA MEDAN - Ryu, Ryu; Nasution, M. Amri; Antoro, Budi (Journal Economic Management and Business, 2025)
This study aims to analyze the influence of machine maintenance and just-in-time production on production volume at PT. Lambang Utama Medan, a leading manufacturer of cream and bar soap. The research adopts a quantitative approach with a sample of 60 respondents selected from 151 production employees using Slovin's formula. Data collection techniques include observation, interviews, questionnaires, and documentation. The data were analyzed using multiple linear regression, along with validity tests, reliability tests, classical assumption tests, t-test, F-test, and the coefficient of determination (R²).The findings indicate that machine maintenance has a positive and significant effect on production volume (t = 1.965; p < 0.05), as does just-in-time production (t = 2.414; p < 0.05). Simultaneously, both variables significantly affect production volume (F = 7.446; p < 0.05), with an adjusted R² value of 0.751, meaning that 75.1% of the variance in production volume can be explained by these two variables. The study concludes that effective machine maintenance and the implementation of timely production schedules are crucial in optimizing and sustaining production volume. These findings provide valuable insights for operational management strategies and contribute to the academic development of production and efficiency studies in manufacturing industries.